Influence of distributive justice on organizational citizenship behaviors: The mediating role of gratitude - Bala Subramanian, R.; Srikanth, P. B.; Thakur, Munish (Frontiers in Psychology, 2022)
Distributive justice is known to have important emotional and affective outcomes. The present study explores the role of distributive justice as an antecedent to feelings of gratitude toward the organization. Borrowing from social exchange theory, we investigate the mediating role of gratitude in the relationship between “perceived fairness in distributive justice” and “employees’ organization citizenship behaviors (OCB).” Time-lagged, multi-source data was collected from 185 employees and their supervisors employed in a large manufacturing organization based in East India. Two significant findings emerge. First, the results indicate that feelings of gratitude signal fair distribution of benefits such that the employees go beyond the call of the duty to invest in OCB. Second, engagement in such acts seems to nullify their social debts highlighted in the social exchange perspective. Thus, a strong moral emotion, gratitude is a powerful vehicle that drives employees to act in the organization’s interests because doing is desirable and rightful. Implications for theory and practice are discussed.